2005
DOI: 10.1073/pnas.0501179102
|View full text |Cite
|
Sign up to set email alerts
|

Subnets of scale-free networks are not scale-free: Sampling properties of networks

Abstract: Most studies of networks have only looked at small subsets of the true network. Here, we discuss the sampling properties of a network's degree distribution under the most parsimonious sampling scheme. Only if the degree distributions of the network and randomly sampled subnets belong to the same family of probability distributions is it possible to extrapolate from subnet data to properties of the global network. We show that this condition is indeed satisfied for some important classes of networks, notably cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
393
4
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 472 publications
(424 citation statements)
references
References 15 publications
17
393
4
2
Order By: Relevance
“…Similar conclusion has been drawn on random node sampling in [17]. Therefore disease propagation in the sampled subnet reveals some different features from those in the original networks, as we shall discuss below.…”
Section: Contact Network With Fear Factorsupporting
confidence: 51%
“…Similar conclusion has been drawn on random node sampling in [17]. Therefore disease propagation in the sampled subnet reveals some different features from those in the original networks, as we shall discuss below.…”
Section: Contact Network With Fear Factorsupporting
confidence: 51%
“…a power law) over much of their range, are in fact better fit with an exponential or other degree distribution [20,21]. Another problem, only recently pointed out [22], is that many of these networks are in fact samples (often rather small samples of 10% to 20%) of the full network in question. But samples from SF networks are not SF.…”
Section: Kinds Of Networkmentioning
confidence: 99%
“…Conversely, if the observed sample is SF, then the full network is not. Indeed, a random sample from a network will not have the same degree distribution as the whole, except when the 'parent network' is a binomial or negative binomial network (of which Erdos-Renyi and exponential are special cases) [22].…”
Section: Kinds Of Networkmentioning
confidence: 99%
“…This is not necessarily true. Stumpf et al [32] have shown that such a sample accurately characterizes the full network if, and only if, the degree distribution is binomial (i.e. has a generating function G(x) = [1 + m(1 − x)/k] −k , where k can be negative or positive).…”
Section: Some Caveatsmentioning
confidence: 99%